Das interfaces às interações: design participativo do portal BRoffice.org - Amstel, Frederick Marinus Constant Van (2008)
The complexity of communication processes mediated by technology has attracted attention to several areas. In a pragmatic perspective, Interaction Design strives for designing these medias for a particular community, however this process occurs within a political scenario of cultural conflicts. The option of participatory design advocates the individual´s autonomy to develop social uses of techniques, while the Free Software movement specifies legal and organizational criteria to make this possible. The convergence of both these visions in the context of collaborative websites makes it necessary to consider production and use processes as a whole, just as in the mediation concept by Jesús Martín-Barbero. To investigate possible contributions by these approaches, this text includes a case study of a participatory process of a Free Software community website redesign, involving specialists, collaborators and users. Visual identity of the website, its services and organization of information were discussed with the community by using channels such as discussion lists, wiki, audioconferences, and chats. The synthesis of discussions led to a new strategy for presenting products — emphasizing its practical benefits — and dealing with users — who would have easier access to available services. Based on these discussions, several models were elaborated for development of the new website.